Superior thermoelectric properties through triangular triple quantum dots (TTQD) attached to one metallic and one superconducting lead. Issue 4 (1st February 2023) - Yao, Hui; Cheng, Cai-Ping; Li, Li-Li; Guo, Rui; Guo, Yong; Zhang, Chao
Abstract : We theoretically investigate the properties of the N-TTQD-S system: thermoelectric coefficients strongly depend on the ratio of superconducting gap to interdot coupling, as well as asymmetry and interference effects. Abstract : We theoretically investigate the thermoelectric transport properties of triangular triple quantum dots (TTQD) with the central quantum dot coupled to one metallic and one superconducting lead. The system shows significantly superior thermoelectric performance over parallel coupled triple quantum dots and those coupled to two conventional metallic leads. The thermoelectric coefficients strongly depend on the ratio of superconducting gap to interdot coupling, as well as asymmetry and interference effects. The thermopower exhibits single-platform and double-platform structures for different ratios of superconducting gap to interdot coupling. The thermopower and figure of merit achieve quite remarkable values near the superconducting gap edges where the single-particle tunnelling occurs. For symmetric coupling, the maximal figure of merit might reach the order of 10 2 when the superconducting gap is about half that of the interdot coupling. Moreover, the figure of merit can be further greatly enhanced by appropriately matching the electrode coupling asymmetry and interdot coupling asymmetry.